Comparative Advantage and the Distributions of Earnings and Abilities - Sattinger, Michael (Econometrica, 1975)
[A model is developed to describe the allocation of laborers to tasks. The relation between the distributions of earnings and abilities is found to depend on the presence of comparative advantage. Various features of the distribution of earnings are explained in terms of the time taken by a given grade of labor to perform a task of a given difficulty.]